2021
DOI: 10.33824/pjpr.2021.36.4.28
|View full text |Cite
|
Sign up to set email alerts
|

Social Isolation, Illness Anxiety, and Quality of Life in Corona Survivors

Abstract: The aim of this study was to investigate the relationship between social isolation, illness anxiety and quality of life in corona survivors. This paper focuses on moderating role of illness anxiety on the relationship between social isolation and quality of life of COVID-19 survivors who faced this disease in past 6 months. The sample comprised of 110 survivors of COVID-19. Purposive sampling was used to assess the participants with the help of Google forms. Social isolation was measured by using Lubben Social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The results showed that the level of psychological anxiety among the individuals of the study sample was medium for the total degree and the subdimensions. This finding agreed with Shahid et al (2021), which suggested that being committed to the healthy protocol, imposing physical distancing and the individuals' desire to take the medical vaccines against the coronavirus contributed to reducing the state of panic and fear relating to the pandemic. The study results revealed that the degree of professional performance was medium since individuals vary in the level of their professional performance according to their dispositions, the nature of stressors to which they are exposed, their previous experiences, psychological health, and personalities.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results showed that the level of psychological anxiety among the individuals of the study sample was medium for the total degree and the subdimensions. This finding agreed with Shahid et al (2021), which suggested that being committed to the healthy protocol, imposing physical distancing and the individuals' desire to take the medical vaccines against the coronavirus contributed to reducing the state of panic and fear relating to the pandemic. The study results revealed that the degree of professional performance was medium since individuals vary in the level of their professional performance according to their dispositions, the nature of stressors to which they are exposed, their previous experiences, psychological health, and personalities.…”
Section: Discussionsupporting
confidence: 82%
“…In the investigation conducted by Shahid et al (2021), the primary objective encompassed the discernment of the interconnection existing amid social isolation, health-related apprehension concerning diseases, and prevailing lifestyles amid the backdrop of the COVID-19 pandemic. The study enlisted a cohort comprising 110 individuals who had successfully recuperated from COVID-19, selected through a purposive sampling technique.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although social isolation can occur at any stage of life ( 36 – 38 ), previous studies have mostly focused on the older population ( 9 , 39 – 41 ) and, in view of the absolute number of studies, have not very intensely investigated this concern in the young population. In addition, some of studies have been conducted on social isolation and mental health outcomes since the outbreak of COVID-19 ( 42 44 ). However, these studies have focused more on objective quantification of social activities, lack of jobs, and social networks on single dimension ( 39 , 45 , 46 ).…”
Section: Introductionmentioning
confidence: 99%